Studies on Fruit Infestation and Biology of Gall Psyllid Trioza fletcheri Minor Crawford (Triozidae) on Terminalia elliptica Willd. (Combretaceae) in South India - C , Rajesh.; Jacob , John Prasanth; K.N , Ashrith. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Terminalia elliptica Willd. commonly as called Indian laurel is a deciduous tree of the family Combretaceae and found native to South and South- East Asia. The tree is mainly harvested for the hard wood timber, ethno medicine, tannin extraction and also used as the primary hosts for the production of good quality tasar silk in Central India. The tree is attacked by several insect pests among them leaf gall infestation by the psyllid T. fletcheri cause severe economic loss to tasar silk cultivation. The present study documented the occurrence of gall infestation on the flowers and fruits of T. elliptica by T. fletcheri. The psyllid usually induces galls in leaves and stem of T. elliptica. This is the first report of psyllid T. fletcheri inducing galls on flowers and fruits of T. elliptica. Infestation level in few locations in Western Ghat forest areas of Kerala and Tamil Nadu is assessed. Biology of the gall insect is also studied. The impact of psyllid infestation in the flowers and fruits on the seed production of this important tree species is discussed.